Measurement of Embodied CO2Emissions and Decomposition of Influencing Factors in Foreign Trade: A Case Study of China - Wu, Sanmang; Li, Shantong (Journal of Environmental Accounting and Management, 2026)
In this study, we measured the embodied CO2emission and analyzed the flow direction of embodied CO2 in China’s foreign trade among the trade partners using a multi-national input-output model based on noncompetitive input-output tables, national input-output tables developed by the Organization for Economic Cooperation and Development, and CO2 emission strength listed in the Global Trade Analysis Program (GTAP) version 7.0 for the years 2002, 2005, and 2010. Using a structural decomposition method, we analyzed the changes in the embodied CO2emissions in China’s foreign trade were caused bythe three factors:export scale and structural changes, intermediate structural changes in the input-output table, and CO2emissions per unit of output. According to our results, from 2002 to 2010, China’s foreign trade created a huge trade surplus and a large embodied CO 2 deficit. In 2010, the CO2surplus reached 1.012 billion t. The rapid growth of trade scale was the main factor in the increase of embodied CO2in China’s export trade, and the technique effect brought about by the decrease in CO2emission strength is a significant factor in restraining the increase of embodied CO2in export trade.